Benzoxazole or Benzothiazole as an Innate Directing Group for Palladium- and Ruthenium-Catalyzed Complementary C–H Arylation: Functionalization of Biorelevant Heterocyclic Scaffolds - Maingle, Mohit; Sunny, Steeva; Sheeba, Loddipalle; Pathan, Firojkhan Rajekhan; Seth, Kapileswar (Synthesis, 2023)
The benzoxazole and benzothiazole moieties were used as innate directing groups for Pd(II)- and Ru(II)-catalyzed C–H arylation of the biorelevant heterocycles 2-arylbenzoxazole and 2-arylbenzothiazole with diverse iodoarenes; palladium and ruthenium catalysis could be used complementarily. The use of σ-donor ligands, such as N,N-dimethylacetamide in the Pd(II) catalytic cycle, and σ-donor/π-acceptor ligands, such as PPh3 in the Ru(II) catalytic cycle, enhanced the arylation rate significantly and was governed by the C–H acidity of the C2-aryl ring of the 2-arylbenzoxazole or 2-arylbenzothiazole. These approaches have a broad substrate scope with respect to coupling partners, to accommodate electron-neutral, electron-rich, as well as electron-deficient iodoarenes; the C2-aryl unit of the 2-arylbenzoxazole or 2-arylbenzothiazole exhibited a high degree of site selectivity at the ortho C–H position, affording only monoarylated derivatives in decent yields; the reactions are functional-group-tolerant and applicable to gram-scale production.
Keywords: innate/native directing group; palladium catalysis; ruthenium catalysis; complementary C–H activation; monoarylation; biosignificant scaffolds; site selectivity